War, Federalism, and Survival Ukraine’s Struggle for A Sustainable Political Order - Kuznetsov, Michael Yurievich (Universitas Airlangga, 2025)
The ongoing war in Ukraine (from 2014 to today) has exposed the vulnerabilities of its centralized governance system, reigniting debates about federalism as a potential solution for national unity and stability. Federalism’s potential to reshape Ukraine’s geopolitical position is critical in the context of its ongoing war and shifting global dynamics. By July 2025, Ukraine faces a complex geopolitical landscape, with waning Western support and persistent Russian aggression. Federalism, as proposed by the Steinmeier Formula, could weaken Russia’s pretext for intervention by addressing regional grievances, align with EU membership criteria, and reduce reliance on NATO’s military aid, offering a path to sustainable peace. Ukraine’s unitary governance model has struggled to reconcile the divergent identities of its western (Ukrainian-speaking) and eastern (Russian-speaking) regions. The 2014 referendum of Crimea and the war in Donbas highlighted the risks of centralized rule, where regional grievances escalate into violent separatism. Despite the Minsk agreements and diplomatic efforts, a sustainable resolution remains elusive. The conflict, particularly in the eastern regions, underscores the challenges of managing linguistic, cultural, and political diversity under a unitary state structure. The “Steinmeier Formula,” proposed in 2015, suggested federalism as a means to resolve regional tensions, yet the idea remains contentious. Federalism offers Ukraine a path to stability by balancing regional autonomy with national unity. Successful models (Switzerland, India) demonstrate its viability. Without structural reforms, Ukraine risks fragmentation, economic ruin, and prolonged conflict. Policymakers must weigh federalism’s risks against the greater danger of inaction. Keywords: Federalism, Ukraine conflict, Steinmeier Formula, Decentralization, Regional autonomy